Evolutionary Perspectives on Child Development and Education - Geary, David C.; Berch, Daniel B. (Evolutionary Psychology, 2016)
This stimulating volume assembles leading scholars to address issues in children's cognitive, academic, and social development through the lens of evolutionary psychology.Debates and controversies in the field highlight the potential value of this understanding, from basic early learning skills through emerging social relationships in adolescence, with implications for academic outcomes, curriculum development, and education policy.Children's evolved tendency toward play and exploration fuels an extended discussion on child- versus adult-directed learning, evolutionary bases are examined for young learners' moral development, and contemporary theories of learning and memory are viewed from an evolutionary perspective.Along the way, contributors' recommendations illustrate real-world uses of evolution-based learning interventions during key developmental years. Among the topics covered: The adaptive value of cognitive immaturity: applications of evolutionary developmental psychology to early education Guided play: a solution to the play versus learning dichotomy Adolescent bullying in schools: an evolutionary perspective Fairness: what it isn't, what it is, and what it might be for Adapting evolution education to a warming climate of teaching and learning The effects of an evolution-informed school environment on student performance and wellbeing Evolutionary Perspectives on Child Development and Education will interest researchers and graduate students working in diverse areas such as evolutionary psychology, cultural anthropology, human ecology, developmental psychology, and educational psychology. Researchers in applied developmental science and early education will also find it useful.